Learning from experience in Hangzhou: WLCE leisure experience research opportunity. Issue 2 (2nd April 2020) - Bastiaansen, Marcel; Young, Marie; Verdet, Isabel; Elekes, Zsombor; Fransen, Storm; Jiaqi, An; Li, Qian; Proveyer, Maria-Liz; Ribeiro da Silva, Leandro; Wang, Yan; Wang, Zhe; Yang, Yinghui; et al.
ABSTRACT: This text was collaboratively written by the 12 students – from Brazil, Canada, China, Hong Kong and Hungary – who participated in the WLCE Leisure Experience Research Opportunity, a fieldwork project focusing on resident, national and international visitors to the Chinese city of Hangzhou. The project, designed and implemented by the WLO, was supported by the Hangzhou Municipal Bureau of Commerce and Hangzhou Commerce and Tourism Group, and supervised by Dr. Marcel Bastiaansen (Breda University of Applied Sciences, the Netherlands), Dr. Marie Young (University of the Western Cape, South Africa) and Dr. Isabel Verdet (WLO Secretariat) .